Semantic Analysis Of Meaning In The Lyrics Of The Song "Life Too Short" By Aespa - Andi Musyahidah Mawaddah; Rahmat, Subhan (Strata Social and Humanities Studies, 2023)
The scope of study on semantic analysis of meaning in song lyrics will involve analyzing the words and phrases used in the lyrics to understand the deeper meaning and emotions that the singer wants to convey to the listeners. This study was conducted with the aim of finding out and describing what types of meaning are contained in the lyrics of Aespa's song "life too short" based on semantic meaning studies. This study is a descriptive qualitative research where the object of this research is in the form of the text of a song entitled "life too short" by a South Korean girl group singer, namely Aespa. The method of obtaining data in this research involved utilizing a literature review approach. The lyrics of Aespa's song "life too short" were obtained from the internet. Afterward, the writer discerns the nature of the message conveyed in different segments of the song. After being analyzed based on the theory of Prof. Dr. D. Wagiman Adisutrisno, M. A. (2008), the results of this study indicate that in Aespa's song "life too short" there are two types of meaning that emerge, namely conceptual meanings and idioms. This study can provide insight of the theme and messages conveyed by the song. Keywords : Semantics, Conceptual, Idioms, Lyrics, song